The Personal and Political Response in W.B Yeat's "Easter 1916" - Muslih, Waleed Shihan (International Journal of Psychosocial Rehabilitation, 2020)
One of the troubling issues in "Easter 1916" by William Butler Yeats (1865-1939) is the use of some ambiguous expressions by the poet in presenting the subject matter of the poem. This ambiguity reflects a duality in the poet's attitude towards the events in 1916. He is not completely consistent with the revolutionaries. In some parts of the poem, the poet is with the Irish rebels whereas in other parts of the poem he is against them. However, the present paper aims at studying the reason behind the poet's dual attitude in the poem. In terms of methodology, the present paper gives a summary of the poem then it moves to some different aspects of poetic reaction and situations such as rational versus emotional, individual prejudice, and conformity. The study found out that the ambivalence in "Easter 1916" is caused by the intervention between the poet's personal and the political visions.